Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Kerajinan Keris: Studi Perilaku Konsumen - Pratama Nugraha, Budi Sutiono; Wahyudi, Rudy; Kusumawardhani, Devi (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This research aims to identify the factors influencing the purchasing decisions of keris craft through a consumer behavior study. Keris craft, as an integral part of cultural heritage, faces challenges in keeping up with global developments and competing with modern products. Factors such as price, product quality, cultural value, and design are considered to play a significant role in consumer decision-making.This research employs a mixed-method approach, combining qualitative and quantitative methods using structured questionnaires and interviews. The analysis results indicate that price and product quality significantly influence purchasing decisions, while cultural value and design also emerge as key factors shaping consumer preferences for keris craft.These findings provide in-depth insights for industry practitioners in designing more effective marketing strategies. Awareness of cultural values and appreciation for traditional design opens opportunities to enhance product attractiveness. Practical implications of this research include the development of competitive pricing strategies, improvement of product quality, and an emphasis on cultural values to garner consumer preference.This study not only contributes to understanding consumer behavior in the context of keris craft but also provides a foundation for further research in comprehending the dynamics of marketing traditional cultural products